PENGARUH METODE PEMBELAJARAN TGT TERHADAP KEMAMPUAN BERBAHASA MANDARIN SISWA SMP METHODIST CHARLES WESLEY MEDAN - Ivana Ivana (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Learning Method is a way that is done by a teacher so that learning processes occur in students to achieve learning goals. This study aims to know significantly the influence of the Team Games Tournament learning method on the ability to recognize vocabulary about nouns students of Medan Charles Wesley Methodist Middle School. The learning material taught to students of Medan's Charles Wesley Methodist Middle School is a book from Taiwan, namely Hello, åŽè¯! which is a Chinese language textbook at the Medan Charles Wesley Methodist Middle School. This research was conducted in the school of Charles Wesley Methodist Middle School in Medan, specifically 7th grade students of junior high school, namely classes 7A and 7B. The research design used was a quantitative research design. The analysis of the results of the research used is the analysis of the t-test. The results of this study indicate that the Team Games Tournament learning method significantly influences the mandarin language skills of Medan Charles Wesley Methodist Middle School students